Influence of opposition on ball velocity in the handball jump throw - Rivilla-Garcia, J.; Grande, I.; Sampedro, J.; van den Tillaar, R. (Journal of Sports Science & Medicine, 2011)
The purpose of the present study was to investigate the influence of different degrees of opposition on ball velocity in the jump throw in elite, amateur and adolescent team handball players. Thus, one hundred and nineteen elite, amateur and under 18 team handball players performed jump throws under three different conditions: 1) without opposition, 2) with the opposition of the goalkeeper and 3) with the opposition of the goalkeeper and a defensive player. The degree of opposition was found to have a negative effect on ball velocity in all three groups (p < 0.001). Furthermore, the level of competition had a positive effect on ball velocity (p < 0.001). However, no interaction was found between the level of competition and the degree of opposition on ball velocity (p = 0.178). The findings of this study indicate that an increase of external stimuli probably influences throwing kinematics and thereby maximal ball velocity. However, experience does not seem to be a factor that can reduce the influence of these external stimuli.